Strengthening Digital Literacy for Students As An Effort To Reject Radical Movements - Farhan, Ahmad; Muis, Andi Abd.; Ali, Makhrus (Rumah Riset Publisher, 2023)
This article describes the urgency of strengthening digital literacy for students as a deployment to carry out online deradicalization. As a student, they must be the core actors in many things competing ideas on social media, they must be given soft skills and hard skills in digitizing technology, especially those related to information media. A Santri must be resourceful in presenting content that carries the theme of Islamic mercy and takes a strategic role in online deradicalization. This research is a qualitative research using a literature method that analyzes literature and sources related to theme research. This article explains how to strengthen digital literacy for students in Pesantren through these steps. Santris are taught how to package religious messages or proselytizing with attractive packaging and easy-to-understand language so that they read more and more.